Do Islamic Banks Act ‘Islamic’ During COVID-19 Pandemic? - Shaharuddin, A. (Universiti Sains Islam Malaysia, 2024)
The world is currently experiencing the most unprecedented health crisis. As of June 2020, the Corona disease has infected more than 8 million people and caused 465,000 deaths worldwide. The world economy is also impacted by the Corona virus pandemic known as COVID-19. Malaysian government estimates that the economic losses since the enforcement of national lockdown amounts to RM63 billion. Subsequently, a huge stimulus package worth RM250 billion was distributed to sustain the domestic markets. In addition, individuals and businesses were offered moratorium which gives six months deferment of installment to cope with financial challenges during this difficult time. The implementation of moratorium however raises a polemic within the Islamic banking industry locally. Customers question the justification used by Islamic banks in imposing additional charges after the expiry of moratorium period. The criticism to certain extend has labelled Islamic banks similar with their conventional counterparts for prioritizing profit over social responsibility. Thus, the article analyzes the moratorium issue based on the framework of Shariah objectives (maqasid). The analysis will not only shed light on the current moratorium polemic but also provides a comprehensive view for the broader issue pertaining to the dichotomy between the theory and practice of Islamic banking industry.